(untitled) (Experimental biology, 2020)
The article presents the physical, chemical and microbiological quantitative and qualitative characteristics of phosphorus-containing man-made waste (slags and sludges) of the former Shymkent phosphorus plant in the South of Kazakhstan. The study found that slurries and slags of phosphorus-containing waste have a pH of 6-7,5 and such components as SiO2-quartz, CaCO3 –calcite, and Fe2O3 –hematite predominate in the composition of surface eroded waste. The following groups of microorganisms were identified in the composition of phosphorus waste: micromycetes in quantity (5,4±0,5)×10CFU/g, heterotrophs-in the amount of–(3,8 ±0,3) ×104 CFU/g, phase 1 nitrifiers -108 CFU / g, nitrogen-fixing bacteria-in quantity 90 % fouling of lumps, actinomycetes-in quantity 105 CFU/g, enterobacteria-in quantity 107 CFU/g. Anaerobes in slag samples -3, 8x104 CFU / ml, and in sludge samples -0, 50x102 CFU / ml, that is, the number of anaerobic microorganisms is less than aerobes.Thionic and sulfur-oxidizing bacteria were not detected in the phosphorus-containing waste. As a result of screening work, 73 isolates of microorganisms that are promising for biogeotechnological purposes were isolated. Keyword: microorganisms, bio-leaching, phosphorus-containing waste, slag, sludge.